Randomized, Multicenter Study to Assess the Effects of Different Doses of Sildenafil on Mortality in Adults With Pulmonary Arterial Hypertension - Hoeper, Marius M; Ewert, Ralf; Jansa, Pavel; Sirenko, Yuriy; Skride, Andris; Balagtas, Cecile; Hackley, Sarah; Vogt, Susanne; Abreu, Paula; Haughie, Scott; Hassan, Tarek; Oudiz, Ronald J (Circulation, 2024)
BACKGROUND: Sildenafil, approved for pulmonary arterial hypertension (PAH), has a recommended adult dose of 20 mg TID, with a previously approved 5-mg TID dose by the US Food and Drug Administration. Safety concerns arose because of common off-label use of higher doses, particularly after pediatric data linked higher doses to increased mortality. To assess this, the Food and Drug Administration mandated a study evaluating the effects of various sildenafil doses on mortality in adults with PAH. METHODS: This randomized, double-blind study compared sildenafil at doses of 5, 20, or 80 mg TID in adults with PAH. The primary objective was noninferiority of 80 mg of sildenafil versus 5 mg for all-cause mortality. Secondary end points included time to clinical worsening and change in 6-minute walk distance at 6 months. Interim analyses were planned at 50% and 75% of the anticipated mortality events. Safety and tolerability were assessed in the intention-to-treat population. RESULTS: The study was halted after the first interim analysis, demonstrating noninferiority for 80 mg of sildenafil versus 5 mg. Of 385 patients enrolled across all dose groups, 78 died. The primary analysis showed a hazard ratio of 0.51 (99.7% CI, 0.22-1.21; P<0.001 for noninferiority) for overall survival comparing 80 mg of sildenafil with 5 mg. Time to clinical worsening favored 80 mg of sildenafil compared with 5 mg (hazard ratio, 0.44 [99.7% CI, 0.22-0.89]; P<0.001). Sildenafil at 80 mg improved 6-minute walk distance from baseline at 6 months compared with 5 mg (least square mean change, 18.9 m [95% CI, 2.99-34.86]; P=0.0201). No significant differences were found between 80 mg of sildenafil and 20 mg in mortality, clinical worsening, and 6-minute walk distance. Adverse event-related drug discontinuations were numerically higher with 80 mg of sildenafil. CONCLUSIONS: Sildenafil at 80 mg was noninferior to sildenafil at 5 mg when examining all-cause mortality in adults with PAH. Secondary efficacy end points favored 80 mg of sildenafil over 5 mg. On the basis of these findings, the Food and Drug Administration recently revoked the approval of 5 mg of sildenafil for adults with PAH, reinforced 20 mg TID as the recommended dose, and now allows dose titration up to 80 mg TID, if needed. REGISTRATION: URL: https://www.clinicaltrials.gov; Unique identifier: NCT02060487.
Keywords: dospělí; safety; inhibitory fosfodiesterasy 5; vztah mezi dávkou a účinkem léčiva; Female; Hypertension, Pulmonary; Sildenafil Citrate; vazodilatancia; Adult; pulmonary arterial hypertension; výsledek terapie; ženské pohlaví; Walk Test; sildenafil citrate; lidé; test chůzí; dvojitá slepá metoda; Treatment Outcome; survival; plicní arteriální hypertenze; sildenafil citrát; Vasodilator Agents; Dose-Response Relationship, Drug; Double-Blind Method; Male; Phosphodiesterase 5 Inhibitors; Aged; Pulmonary Arterial Hypertension; plicní hypertenze; lidé středního věku; mortality; senioři; mužské pohlaví; Middle Aged; Humans